Forms Of Money Laundering Crimes In The Perspective Of The Money Laundering Crime Law In Indonesia - Andre Yosua M; Muhammad Gastari (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Today's crimes are increasingly showing increasingly modern patterns, one of which is the crime of money laundering (